PSYCHOLOGICAL FEATURES OF THE DEVELOPMENT OF MANAGEMENT COMPETENCIES OF STUDENTS - Ruzikulova A.T. (American Journals Publishing, 2023)
This article covers the characteristics of the development of student management competencies, the fact that a competency-based approach in education involves ideas of professional and general, intellectual development, and forms of interdependence and metasubject, which embody correlations.
Keywords: Cognitive experience, cognitive, metacognitive component.